2022
DOI: 10.1002/app.52166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma treatment parameters on the interfacial joining strength of overmolded hybrid fiber reinforced thermoplastic composites

Abstract: In this study, hybrid fiber reinforced thermoplastic composites (hybrid thermoplastic composites) with high interfacial joining strength were fabricated using a plasma treatment strategy and injection overmolding technique. A series of experimental investigations were carried out to ascertain the effects of various plasma treatments on the interfacial joining strength of the overmolded hybrid composites. Test results reveal that compared with the untreated continuous fiber reinforced thermoplastic (CFRT) subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Park et al pre-treated a hydrophobic coating with plasma selectively and observed that by controlling the plasma treatment time the wettability and therefore the droplet spreading diameter of the ink can be controlled [128]. The functionalized surface of a plasma-treated substrate diminishes over time [129] and depends on various process parameters such as treatment time or gas [130]. Other methods for modification, such as surface roughening and abrasive, liquid chemical processes can be used to treat polymer surfaces as well [131].…”
Section: Droplet/substrate Interactionmentioning
confidence: 99%
“…Park et al pre-treated a hydrophobic coating with plasma selectively and observed that by controlling the plasma treatment time the wettability and therefore the droplet spreading diameter of the ink can be controlled [128]. The functionalized surface of a plasma-treated substrate diminishes over time [129] and depends on various process parameters such as treatment time or gas [130]. Other methods for modification, such as surface roughening and abrasive, liquid chemical processes can be used to treat polymer surfaces as well [131].…”
Section: Droplet/substrate Interactionmentioning
confidence: 99%
“…[15][16][17] For overmolded thermoplastic composites, although hybrid components with comprehensive mechanical properties can be obtained via injection, there are disadvantages of lower interface strength and more process steps. [18][19][20] With regard to this phenomenon, some scholars tried to fabricate continuous fiber reinforced thermoplastics by injection molding process. Solorza-Nicolas et al [21] proposed to obtain woven glass fiber reinforced polycarbonate composites by injection compression molding technique, simulated the behavior of the polymer during the filling process, and studied the fiber orientation distortion with different laying modes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15–17 ] For overmolded thermoplastic composites, although hybrid components with comprehensive mechanical properties can be obtained via injection, there are disadvantages of lower interface strength and more process steps. [ 18–20 ]…”
Section: Introductionmentioning
confidence: 99%